2023
DOI: 10.7554/elife.81629
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the immune repertoire of a humanised transgenic mouse through immunophenotyping and high-throughput sequencing

Abstract: Immunoglobulin loci-transgenic animals are widely used in antibody discovery and increasingly in vaccine response modelling. In this study, we phenotypically characterised B-cell populations from the Intelliselect® Transgenic mouse (Kymouse) demonstrating full B-cell development competence. Comparison of the naïve B-cell receptor (BCR) repertoires of Kymice BCRs, naïve human, and murine BCR repertoires revealed key differences in germline gene usage and junctional diversification. These differences result in K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Interestingly, our findings suggest that the Kymouse (humanized mice) dataset under investigation undersampled the human dataset, both with respect to developability (Figure 7B) and sequence spaces (Supp. Figure 10B), even though lower-level features such as VDJ gene usage and CDR3 length were previously found to overlap (82).…”
Section: Relevance Of Species-and Chain-specific Developability Space...mentioning
confidence: 70%
“…Interestingly, our findings suggest that the Kymouse (humanized mice) dataset under investigation undersampled the human dataset, both with respect to developability (Figure 7B) and sequence spaces (Supp. Figure 10B), even though lower-level features such as VDJ gene usage and CDR3 length were previously found to overlap (82).…”
Section: Relevance Of Species-and Chain-specific Developability Space...mentioning
confidence: 70%
“…It was previously shown that the targeted VRC01-class BCRs are approximately 300 to 900-fold less frequent in this mouse model than in humans 35 , therefore making this model less suitable to test the induction of VRC01-class B cells. In addition, long HCDR3s, which are a requirement for several HIV bnAb classes 52 , have been shown to be less comon in Kymice than in humans 49 , thus complicating testing of bnAb induction in these animals. However, despite differences in the frequencies of specific lineages, the overall BCR repertoire in Kymice mice is comparable to humans 48,49 , therefore making this system suitable to investigate “off-target” B cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long HCDR3s, which are a requirement for several HIV bnAb classes 52 , have been shown to be less comon in Kymice than in humans 49 , thus complicating testing of bnAb induction in these animals. However, despite differences in the frequencies of specific lineages, the overall BCR repertoire in Kymice mice is comparable to humans 48,49 , therefore making this system suitable to investigate “off-target” B cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations